ZnO Applications and Challenges - OKTAR, FAİK NÜZHET (BENTHAM SCIENCE PUBL LTD, 2014)
Metal oxide nanoparticles represent a new class of important materials that are increasingly being developed for use in research and health-related applications. Although the in vitro antibacterial activity of zinc oxides and some other zinc compounds has been known for quite some time, only in the last few years nanoparticles of ZnO have been investigated for their antibacterial activity, the knowledge about it remaining deficient. The antimicrobial activity of ZnO nanoparticles is strongly influenced by some factors such as size and the presence of light. The potential applications include, but are not limited to, topic drugs, cosmetics or component for agents that control the spread of bacterial strains (antibacterial paint in hospitals, antibacterial coatings for fabrics, antibacterial packaging for food, etc). The current review aims to present the level of knowledge accumulated on the antibacterial and antifungal activity of ZnO.
Keywords: ZnO nanoparticles; antibacterial activity; antifungal activity; METAL-OXIDE NANOPARTICLES; SOLID LIPID NANOPARTICLES; IN-VITRO EVALUATION; ZINC-OXIDE; ANTIBACTERIAL ACTIVITY; ESCHERICHIA-COLI; DOPED ZNO; QUANTUM DOTS; QUANTITATIVE-EVALUATION; PHOTOCATALYTIC ACTIVITY